2019
DOI: 10.1002/ana.25604
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatics Visualization after Focused Ultrasound‐Induced Blood–Brain Barrier Opening in Humans

Abstract: It is currently unclear whether the glymphatic system, a brain‐wide interstitial fluid–cerebrospinal fluid exchange described in rodents, exists in humans. Focal blood–brain barrier disruption using magnetic resonance–guided focused ultrasound allows parenchymal penetration of gadobutrol contrast, creating an opportunity to study glymphatics in vivo noninvasively. We describe patterns of contrast distribution in the perivascular space, subarachnoid space, and space surrounding large veins draining toward the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 22 publications
8
61
0
Order By: Relevance
“…An experimental study using regular FLAIR imaging, which temporarily opened the blood-brain barrier with focused ultrasound (FUS) showed that the amount of GBCA leakage into the subarachnoid space after intravenous injection was increased by FUS. 18 According to the previous report, the leakage around the cortical veins after intravenous injection of GBCA is limited to the perivascular space around the cortical veins at 5 min after intravenous injection, after which it spreads into the surrounding the subarachnoid space. 1 Furthermore, images in which the perivascular space around the cortical veins is directly connected to the meningeal lymphatic vessels near the SSS have been shown.…”
Section: Discussionmentioning
confidence: 97%
“…An experimental study using regular FLAIR imaging, which temporarily opened the blood-brain barrier with focused ultrasound (FUS) showed that the amount of GBCA leakage into the subarachnoid space after intravenous injection was increased by FUS. 18 According to the previous report, the leakage around the cortical veins after intravenous injection of GBCA is limited to the perivascular space around the cortical veins at 5 min after intravenous injection, after which it spreads into the surrounding the subarachnoid space. 1 Furthermore, images in which the perivascular space around the cortical veins is directly connected to the meningeal lymphatic vessels near the SSS have been shown.…”
Section: Discussionmentioning
confidence: 97%
“…Our results highlight the conformal capacity of FUS to safely and repeatedly open the BBB in the hippocampus, with spatial precision and no off-target BBB opening. FUS-mediated BBB opening in preclinical models has been found to promote amyloid-beta clearance, delivery of endogenous antibodies, activation of microglia (8,12), and potential modulation of the glymphatic system (13). The significance with respect to human translation of amyloid reduction observed in animal models with FUS-mediated BBB disruption is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that CSF flows between the BM and astrocyte endfeet of arteries and capillaries, with arteriole pulsations driving bulk fluid flow through the parenchyma, although others have argued about the extent of bulk flow (Abbott et al, 2018; Hladky and Barrand, 2019). This “glymphatic” system helps to clear interstitial solutes such as amyloid via paravenous drainage pathways (Iliff et al, 2012; Xie et al, 2013; Mestre et al, 2018) and has been visualized in human patients via magnetic resonance imaging (MRI; Meng et al, 2019; Fultz et al, 2019). Expression of water channel aquaporin-4 in astrocyte endfeet has been reported to play a critical role in the movement of CSF into the parenchyma (Haj-Yasein et al, 2011; Iliff et al, 2012; Mestre et al, 2018).…”
Section: The Nvumentioning
confidence: 99%